Pengaruh Health Education Menggunakan Metode Paikem Terhadap Kesiapan dan Kemampuan dalam Mengahadapi Menarche Siswi Kelas 5 dan 6 di SD Negeri Wangkal Ii - Hosnol Khotimah; Dodik Hartono; Achmad Kusyairi (STIKes Ibnu Sina Ajibarang, 2025)
Menarche is the first menstruation which usually occurs between the ages of 10-16 years. The arrival of the first menstruation makes teenagers feel unprepared and unable to face menarche due to a lack of knowledge and practice during menstruation. So in this case health education using the LAICEF method is needed. This research aims to determine the effect of health education using the LAICEF method on the readiness and ability to face menarche in grade 5 and 6 female students at Wangkal II Elementary School. This research is a pre-experimental design with a one-group pre-post test approach. The population was 25 female respondents from Wangkal II Elementary School, the 25 samples studied were taken using Total Sampling. The instrument used questionnaire through a process of editing, coding, scoring and tabulating. The data obtained from this research was analyzed using the Wilcoxon Test. The results of this research showed readiness and ability to face menarche during pre-post. The majority of respondents showing readiness results in the pretest were in the poor category, as many as 14 respondents (56%). In the post test data, the majority in the sufficient category were 12 respondents (48%). Meanwhile, the majority of abilities in the pretest were in the poor category, 17 respondents (68%). The majority of post test data were in the sufficient category, 16 respondents (64%). The results of the Wilcoxon test obtained a p value: 0.000 <0.05. This shows that there is an influence of health education using the PAIKEM method on the readiness and ability to face menarche in grade 5 and 6 female students at Wangkal II Public Elementary School. Health education using the LAICEF method can develop female students' innovation and creativity so that providing education on readiness and ability to face menarche can be effective and enjoyable for female students, and female students are not burdened by ongoing learning.